The beach: the making & remaking of Coffee Bay (1945-2005) - Wildman, Kim (African Studies, 2014)
Coffee Bay, a small beach resort located in the heart of the former Transkei, is one of the current tourist ""hot spots"" on South Africa's Wild Coast. Through a detailed analysis of tourist literature spanning several decades, together with consideration of established theories regarding the 'making of place', this study examines the relationship between visual representations of Coffee Bay and the changing patterns of tourism in the seaside resort from 1945 to the present. This study traces the Coffee Bay's development over three separate periods - 1945 to 1969, 1970 to 1989, and 1990 to 2005 - during which time three different groups of tourists inhabited its space: cottage owners, hotel guests and backpackers. Despite their differences, each group sought the same thing an archetypal, mythical vision of a tourist ""paradise"". They thus inhabited and confected Coffee Bay's touristscape with their interpretations of this Utopia.